Zinc alleviates cadmium-induced reproductive toxicity via regulating ion homeostasis, metallothionein expression, and inhibiting mitochondria-mediated apoptosis in the freshwater crab Sinopotamon henanense - Jing Liu; Ermeng Wang; Ziru Cheng; Yuan Gao; Chienmin Chen; Ru Jia; Zhi Luo; Lan Wang (Ecotoxicology and Environmental Safety, 2023)
Cadmium (Cd) is a carcinogenic environmental pollutant that harms male reproductive systems by lowering sperm quality, impairing spermatogenesis, and causing apoptosis. Although zinc (Zn) has been reported to alleviate Cd toxicity, the underlying mechanisms have not been fully elucidated. The aim of this work was to investigate the mitigating effects of Zn on Cd-induced male reproductive toxicity in the freshwater crab Sinopotamon henanense. Cd exposure not only resulted in its accumulation but also in Zn deficiency, decreased sperm survival rate, poor sperm quality, altered ultrastructure, and increased apoptosis in the testis of the crabs. Morever, Cd exposure increased the expression and distribution of metallothionein (MT) in the testis. However, Zn supplementation effectively mitigated the aforementioned effects of Cd, as demonstrated by preventing Cd accumulation, increasing Zn bioavailability, alleviating apoptosis, increasing mitochondrial membrane potential, decreasing reactive oxygen species (ROS) levels, and restoring MT distribution. Moreover, Zn also significantly reduced the expression of apoptosis-related (p53, Bax, CytC, Apaf-1, Caspase-9, Caspase-3), metal transporter-related ZnT1, metal-responsive transcription factor 1 (MTF1), and the gene and protein expression of MT, while increasing the expression of ZIP1 and Bcl-2 in the testis of Cd-treated crabs. In conclusion, Zn alleviates Cd-induced reproductive toxicity via regulating ion homeostasis, MT expression, and inhibiting mitochondria-mediated apoptosis in the testis of S. henanense. The information obtained in this study may serve as the foundation for further investigation into the development of mitigation strategies for adverse ecological and human health outcomes associated with Cd contamination or poisoning.